2009
DOI: 10.1375/brim.10.1.59
|View full text |Cite
|
Sign up to set email alerts
|

Prospective and Retrospective Memory Complaints in Mild Cognitive Impairment and Mild Alzheimer's Disease

Abstract: C urrent management attempts for Alzheimer's disease (AD) focus on the identification of individuals in the preclinical stage. This has led to the development of the diagnostic concept of Mild Cognitive Impairment (MCI), which applies to individuals with declining cognitive abilities but largely preserved everyday functioning. Previous findings indicate that prospective memory deficits are a sensitive marker of preclinical AD and that awareness of prospective memory failures is particularly high, based on its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 69 publications
(85 reference statements)
3
24
0
Order By: Relevance
“…The results indicated that self-rated PM difficulties were equivalent across the three groups [8]. The findings of Eschen et al therefore suggest that the validity of self-report assessment may be limited.…”
Section: Self-report and Informant Report Of Prospective And Retrospementioning
confidence: 99%
“…The results indicated that self-rated PM difficulties were equivalent across the three groups [8]. The findings of Eschen et al therefore suggest that the validity of self-report assessment may be limited.…”
Section: Self-report and Informant Report Of Prospective And Retrospementioning
confidence: 99%
“…When using this encoding strategy particular emphasis should be giving to actions which would be less associated with the context of performance as such actions would, as identified across our results, be less likely to be remembered in the absence of such manipulation. Considering that PM may be particularly affected at an early stage in the development of Alzheimer's Disease (Costa, et al, 2010;Lee et al, 2015), constituting a great object of concern, distress and even frustration not only for these patients but also for their carers (Eschen et al, 2009), and placing at risk individual's social relationships and maintenance of independence (Costa, Carlesimo, & Caltagirone, 2012), the use of motoric encoding might constitute an extremely advantageous tool for PM rehabilitation in prodromal Alzheimer's Disease with positive repercussions in the achievement of a better quality of life for healthy and cognitively impaired older adults.…”
Section: Final Remarksmentioning
confidence: 99%
“…Such prospective memory (PM; Meacham & Leiman, 1982) is especially disrupted in AD (Thompson, Henry, Withall, Rendell, & Brodaty, 2011), presenting a severe threat to the individual's health and social relationships while increasing the burden of care (e.g. Eschen, Martin, Gasser, & Kliegel, 2009;Zogg, Woods, Sauceda, Wiebe, & Simoni, 2012). PM deficits may appear early in the neurodegenerative process (cf.…”
mentioning
confidence: 99%
“…Taken together, these findings are indicative more of a reflection of humor states and personality regarding self-reported memory assessed by PRMQ in an older population than individual differences in memory and cognitive capacity. Eschen et al [35] and Steinberg et al [36] assessed PRMQ utility for an initial MCI screening; amongst its findings MCI patients reported greater prospective and retrospective memory deficits. In a healthy older adults sample, the authors described a higher quantity of subjective prospective memory complaints compared to retrospective memory.…”
Section: Discussionmentioning
confidence: 99%